2010
DOI: 10.1108/09555341011009034
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between spiritual management and determinants of turnover intention

Abstract: PurposeBased on the first part of the service profit chain, the purpose of this paper is to investigate the relationship between 11 spiritual management tactics and determinants of turnover intention.Design/methodology/approachA survey on managers and manufacturing employees is conducted. Later, the grey relational analysis to process the data is used together with the multi‐criteria‐weighted average in the decision‐making process to identify degree of relatedness between spiritual management and determinants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 21 publications
1
16
0
12
Order By: Relevance
“…Lee, Chen, Wang & Dadura (2010) [21], scholars have given intense attention to the subject of employee turnover due to the severity of employee turnover rates in various organizations across the globe and its damaging consequences. Mobley, Horner &Hollingsworth (1978) [22], Turnover intentions is referred to be a conscious and deliberate willfulness to leave the organization.…”
Section: Work Engagement and Turnover Intentionsmentioning
confidence: 99%
“…Lee, Chen, Wang & Dadura (2010) [21], scholars have given intense attention to the subject of employee turnover due to the severity of employee turnover rates in various organizations across the globe and its damaging consequences. Mobley, Horner &Hollingsworth (1978) [22], Turnover intentions is referred to be a conscious and deliberate willfulness to leave the organization.…”
Section: Work Engagement and Turnover Intentionsmentioning
confidence: 99%
“…IC is especially congruent with humanistic, spiritual and emancipatory values (Hodson 2002;Jackson 2002;Sayer 2007;Fernando, Beale and Geroy 2009;Lee, Chen, Wang and Dadura 2010;Marques 2010). However, leaders with instrumental values may also be effective in adopting this style in order to accomplish performance-related organizational goals (Harvey 2001;Jackson 2002;de Lacerda 2010).…”
Section: Individualized Considerationmentioning
confidence: 95%
“…There is a dearth of studies on the effect of spiritual intelligence towards the employees' intention to remain or leave their current organization. A study by [70] found that spiritual intelligence was one of the determinant of employees' intention to stay or leave their current organization. According to the study, there was a difference between the managers and employees' perception concerning the tactics for spiritual management.…”
Section: Relationship Between Spiritual Intelligence and Intention Tomentioning
confidence: 99%